Investor’s preference toward mobile stock trading applications - R . S, Vijaya Kumar; Babu , Harish (BOHR International Journal of Finance and Market Research, 2023)
In the age of digitization, mobile stock trading has gained popularity quickly. This study sought to determine which mobile trading app was the most popular, why users preferred certain trading apps, and what issues users ran into when trading on their mobile apps. To examine the primary data, this study included factor analysis and the Duncan test. The study consists of 85 convenient sampling of Bangalore city. The findings indicate a significant positive relationship between attitude, perceived behavioral control, trading app, more information, network speed and connectivity, superficial benefits, and intention to select mobile stock trading apps. It finds that faith adds enormous descriptive power to perceived behavioral control, mindset, and persuasion in explaining investors’ adoption intention of mobile trading apps.